A State-of-the-Art Review on Conducted Electromagnetic Interference in Non-Isolated DC to DC Converters - Natarajan S.; Sudhakar Babu T.; Balasubramanian K.; Subramaniam U.; Almakhles D.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric discharges; Electromagnetic compatibility; Electromagnetic pulse; Electromagnetic wave interference; Infrared radiation; Power electronics; Radio interference; Atmospheric discharge; Conducted electromagnetic interference; Magnetic interference; Mitigation; Radio frequency interference; State-of-the art reviews; Suppression technique; Terrestrial radiation; DC-DC converters